Role of peptidoglycan recycling enzymes AmpD and AnmK in Acinetobacter baumannii virulence features - Tajuelo, Ana; Terrón, María C.; López-Siles, Mireia; McConnell, Michael J. (Frontiers in Cellular and Infection Microbiology, 2023)
Acinetobacter baumannii is an important causative agent of hospital acquired infections. In addition to acquired resistance to many currently-available antibiotics, it is intrinsically resistant to fosfomycin. It has previously been shown that AmpD and AnmK contribute to intrinsic fosfomycin resistance in A. baumannii due to their involvement in the peptidoglycan recycling pathway. However, the role that these two enzymes play in the fitness and virulence of A. baumannii has not been studied. The aim of this study was to characterize several virulence-related phenotypic traits in A. baumannii mutants lacking AmpD and AnmK. Specifically, cell morphology, peptidoglycan thickness, membrane permeability, growth under iron-limiting conditions, fitness, resistance to disinfectants and antimicrobial agents, twitching motility and biofilm formation of the mutant strains A. baumannii ATCC 17978 ΔampD::Kan and ΔanmK::Kan were compared to the wild-type strain. Our results demonstrate that bacterial growth and fitness of both mutants were compromised, especially in the ΔampD::Kan mutant. In addition, biofilm formation was decreased by up to 69 %, whereas twitching movement was reduced by about 80 % in both mutants. These results demonstrate that, in addition to increased susceptibility to fosfomycin, alteration of the peptidoglycan recycling pathway affects multiple aspects related to virulence. Inhibition of these enzymes could be explored as a strategy to develop novel treatments for A. baumannii in the future. Furthermore, this study establishes a link between intrinsic fosfomycin resistance mechanisms and bacterial fitness and virulence traits.